Gender related differences in brugada syndrome. (14th October 2021) - Cardoso, A; Faria, B; Von Hafe, P; Dias, G; Pereira, T; Ribeiro, S; Calvo, L; Oliveira, M; Fernandes, M; Sanfins, V; Lourenco, A
Abstract: Background: Brugada syndrome (BS) is a heritable channelopathy with male predominance. Males (M) seem to have a higher risk of arrhythmic events, although, there is limited data regarding gender differences in BS. Aim: To compare the differences between genders in a Portuguese sample of BS patients (pts). Methods: Single-center retrospective study of BS pts followed by the Arrhythmology Department. Pts were divided according to gender and compared regarding baseline characteristics and electrocardiographic (ECG) parameters that possibly predict the arrhythmic risk (significative S wave in DI, R wave sign, Tpeak-Tend interval and fragmented QRS). The events during follow-up were syncope of probable arrhythmic origin, ventricular tachycardia/ventricular fibrillation (VT/VF) and sudden cardiac death (SCD). Results: A total of 165 pts were included; 64 (39%) were female (F) and the mean age at diagnosis was 47±15 years. The diagnosis was made by family screening (FS) in 72 (44%) pts. Sixty-seven pts (41%) had spontaneous type 1 pattern, 59 (36%) had history of syncope and 5 (3%) had history of aborted SCD. A positive genetic test was identified in 41 (25%) pts. Sixty-three (38%) pts were referred for an electrophysiological study (EEF) which was positive in 17 (27%) pts. A cardioverter-defibrillator was implanted in 45 (27%) pts. Females were more often diagnosed by FS (64% vs 31%, p <.001), had less type 1 spontaneous pattern (22% vs 53%, p<.001) and had no atrial fibrillation (0% vs 7%, p=.043). They performed EEF less frequently (22% vs 49%, p<.001) and had less spontaneous pattern during treadmill stress test (8% vs 33%, p=.004). Regarding ECG parameters, females had shorter QRS interval (104±12 vs 115±18 ms, p<0.001), less frequent aVR sign (3% vs 27%, p<0.001), less significative S wave in DI (31% vs 55%, p=0.004), and a tendency for a shorter Tp-Te interval (80 vs 100 ms, p=0.051). Corrected QT interval was longer in females (396 vs 392ms, p=0.044). During a median follow-up of 28 (IQR 16–41) months, 7 pts had VT/VF (2F, 5M) and 3 had syncope (3M), with no differences between gender (p=0.287). There were no cardiovascular deaths. Conclusion: In BS, female pts are more often diagnosed by FS and have less spontaneous type 1 pattern. Gender appears to affect basal ECG characteristics in BS, namely in parameters that may predict arrhythmic risk. Further studies are important to clarify the role of gender in prognosis and risk stratification of BS pts. Funding Acknowledgement: Type of funding sources: None.